ANALISIS PEMBUATAN MEDIA GAMBAR PADA MATERI PENGGOLONGAN HEWAN di SD NEGERI 068007 MEDAN TUNTUNGAN - Juniko Esra Tarigan; Nurhayati Surbakti (Universitas Negeri Medan, 2021)
This study aims to improve science learning by using Picture Media on the Theme of Animal Classification at SD Negeri 068007 Medan Tuntungan for the 2020/2021 Academic Year. This study uses a type of quantitative research. The test results of the questionnaire instrument were analyzed to determine the validity and reliability of the use of graphic/image-based learning media in PBM. From the validity test table above, it shows that of the 10 question items obtained from the Google form questionnaire and managed through validity testing with rtable using a significant level of = 0.05 with n = 9, the rtable value of 0.334 states rcount> rtable so that 10 items these are all valid. There are 8 teachers who have made graphic/image-based learning media or 77.8%. There are 8 teachers who have made graphic/image-based learning media using simple materials or 77.8%. 9 teachers stated that making graphic/image-based learning media requires tools and costs. A total of 6 teachers took pictures from the internet in making graphic/image-based learning media and 3 teachers made them manually. A total of 9 teachers stated that students liked the graphic/image-based learning media made by the teacher. A total of 9 teachers stated that the graphic/image-based learning media made by the teacher greatly influenced the improvement of student learning outcomes.Keywords: Making, Media, Image